The Economic Function of The State - Yavuz, Hasan (Turystyka i Rozwój Regionalny, 2018)
The debate over the role of the state in the economy reaches the times when the science of economics has emerged. While the economic activities of the state are inevitable especially in times of crisis, these activities have always been criticized in terms of side effects other than affecting the crisis. This study examines the work done in the literature in terms of public sector size and the failures in economic activities. The reasons for the economic borders of the state, especially under the view of the liberal state, are the most prominent points in the study.